Ocimum sebrabergensis (Lamiaceae), a new species from Namibia - Swanepoel, Wessel; van Jaarsveld, Ernst J. (Phytotaxa, 2019)
Ocimum sebrabergensis, here described as new species, has a restricted range and is only known from the Zebra Mountains within the Kaokoveld Centre of Endemism, northwestern Namibia. These shrubs grow on clayey soil among greyish black rocks of anorthosite. Diagnostic characters for O. sebrabergensis include the mauve-coloured corolla with four orbicular lobes on the posterior lip and the calyx which has the lateral lobes of the anterior lip asymmetric lanceolate. Ocimum sebrabergensis is placed in Ocimum subg. Ocimum sect. Hiantia subsect. Hiantia ser. Serpyllifolium. A comparison of some of the more prominent morphological features to differentiate between O. sebrabergensis and its possible nearest relatives, O. burchellianum and O. fimbriatum, are provided. Based on IUCN Red List categories and criteria, a conservation assessment of Vulnerable (VU D1) is recommended for the new species.